PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA TOKO KIMURA COLLECTION, KUTA UTARA, BADUNG - I Putu Ari Wijaya; Luh Komang Candra Dewi; I Putu Agus Suarsana Ariesta (Universitas Triatma Mulya, 2023)
This study aims to analyze the effect of product quality and price on consumer satisfaction at the Kimura Collection Store, North Kuta, Badung. The number of samples in this study were 100 respondents. The data collection technique used purposive sampling, with the criteria of customers who had shopped at the Kimura Collection Store, North Kuta, Badung. The research method applied in this study is based on multiple linear regression analysis with data collection techniques used are questionnaires, interviews and documentation. The data analysis technique used is quantitative descriptive analysis, validity and reliability test, classical assumption test, multiple linear regression test and t test analysis. The results of the analysis show that the regression results are Y = 1.615 + 0.332X1 + 0.370X2. Product quality (X1) partially has a positive and significant effect on consumer satisfaction (Y), which is shown in the regression coefficient b1X1 of 0.332 with a value of tCount = 4.910 > tTable (0.05: 97) = 1.6606 with sig. t = 0.000 (p < 0.05). Price (X2) partially has a positive and significant effect on consumer satisfaction (Y) which is shown in the b2X2 regression coefficient of 0.370 with a value of tCount = 3.674 > tTable (0.05: 97) = 1.6606 with sig. t = 0.000 (p < 0.05).